Resin composition and product thereof

By using ceramic fillers with high thermal conductivity and prepolymers prepared by prepolymerization reaction in the resin composition, the problem that existing materials cannot have high thermal conductivity and excellent dielectric characteristics at the same time is solved, and the dielectric constant and dielectric are achieved The improvement of many performances such as electrical loss and thermal conductivity are suitable for the improvement of thermal management and stability of electronic equipment.

CN119119729APending Publication Date: 2024-12-13ELITE MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310792283.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2023-06-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing materials cannot simultaneously possess high thermal conductivity and excellent dielectric properties, which makes it difficult for electronic equipment to remain stable under high heat flow density environments and are prone to failure due to overheating.

Method used

Using a resin composition, including 100 parts by weight of a prepolymer and 150 to 200 parts by weight of a ceramic filler, the prepolymer is prepared by prepolymerization reaction of maleimide resin and diamine compound, and the ceramic filler is The thermal conductivity coefficient is greater than 30W/(m.K), so as to improve the characteristics of dielectric constant, dielectric loss, thermal conductivity, tension on copper foil, bending and elongation.

Benefits of technology

The dielectric constant is less than or equal to 5.05, the dielectric loss is less than or equal to 0.0020, the thermal conductivity is greater than or equal to 1.06W/(m.K), the tension force on copper foil is greater than or equal to 4.0lb/in, and the bending is greater than or equal to 323 times. , comprehensive performance improvements with elongation greater than or equal to 10.1% and edge distance greater than or equal to 28 meters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004313952480000021
    Figure BDA0004313952480000021
  • Figure BDA0004313952480000023
    Figure BDA0004313952480000023
  • Figure BDA0004313952480000091
    Figure BDA0004313952480000091
Patent Text Reader

Abstract

The invention discloses a resin composition which comprises 100 parts by weight of prepolymer and 150-200 parts by weight of ceramic filler, the prepolymer is prepared by prepolymerizing a mixture, and the mixture comprises maleimide resin and a diamine compound in a molar ratio of 1: 2 to 2: 1; the heat conduction coefficient of the ceramic filler is greater than 30W / (m.K); and the diamine compound comprises a compound with a structure as shown in a formula (1), a compound with a structure as shown in a formula (2), a compound with a structure as shown in a formula (3) or a combination thereof. The resin composition can be made into a variety of articles, including resin films, prepregs, laminates, or printed circuit boards, with improved one or more characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition, in particular to a resin composition which can be used for preparing a prepreg, a resin film, a laminate or a printed circuit board. Background Art

[0002] The overall power density of today's electronic devices is gradually increasing, but the physical size of electronic devices and electronic components is getting smaller and smaller, resulting in an increase in heat flux density. Therefore, high thermal conductivity materials can be used to achieve stable heat transfer and ensure that heat is less likely to accumulate in the same place. Otherwise, if the heat is blocked and accumulates, the component will fail due to overheating. The prior art has disclosed that fillers with thermal conductivity can be used, but it is impossible to maintain excellent dielectric properties at the same time. Summary of the invention

[0003] In view of the problems encountered in the prior art, especially the inability of existing materials to meet one or more of the above-mentioned property requirements, the main purpose of the present invention is to provide a resin composition and a product made from the resin composition, which can improve at least one or more properties such as dielectric constant, dielectric loss, thermal conductivity, copper foil tension, flange distance, bendability, elongation, etc.

[0004] In order to achieve the above object, the present invention discloses a resin composition, which comprises 100 parts by weight of a prepolymer and 150 to 200 parts by weight of a ceramic filler, wherein:

[0005] The prepolymer is prepared by a prepolymerization reaction of a mixture, and the mixture includes a maleimide resin and a diamine compound in a molar ratio between 1:2 and 2:1;

[0006] The thermal conductivity of the ceramic filler is greater than 30 W / (mK); and

[0007] The diamine compound includes a compound having a structure shown in formula (1), a compound having a structure shown in formula (2), a compound having a structure shown in formula (3), or a combination thereof:

[0008]

[0009] wherein n1 is independently an integer from 6 to 8, and n2 is independently an integer from 5 to 8;

[0010]

[0011] For example, in one embodiment, the ceramic filler includes aluminum oxide, aluminum nitride, silicon carbide, boron nitride, silicon nitride, magnesium oxide, or a combination thereof.

[0012] For example, in one embodiment, the thermal conductivity of the ceramic filler is greater than 30 W / (mK) and less than 320 W / (mK).

[0013] For example, in one embodiment, the mixture is prepolymerized at a temperature of 70 to 150° C. for 1 to 20 hours to obtain the prepolymer.

[0014] For example, in one embodiment, the conversion rate of the maleimide resin and the diamine compound is between 10% and 90%.

[0015] For example, in one embodiment, the maleimide resin includes 4,4'-diphenylmethane bismaleimide, polyphenylmethane maleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 3,3'-dimethyl-5,5'-dipropyl-4,4'-diphenylmethane bismaleimide, m-phenylene bismaleimide, 4-methyl-1,3-phenylene bismaleimide, imide, 1,6-bismaleimide-(2,2,4-trimethyl)hexane, n-2,3-dimethylphenylmaleimide, n-2,6-dimethylphenylmaleimide, n-phenylmaleimide, vinylbenzylmaleimide, maleimide containing a biphenyl structure, maleimide containing an aliphatic long chain structure, a prepolymer of a diallyl compound and maleimide, a prepolymer of a multifunctional amine and maleimide, a prepolymer of an acidic phenol compound and maleimide, or a combination thereof.

[0016] For example, in one embodiment, the resin composition further includes epoxy resin, vinyl polyphenylene ether resin, flame retardant, hardening accelerator, inhibitor, solvent, silane coupling agent, colorant, toughening agent or a combination thereof.

[0017] In addition, the present invention also provides a product made of the above resin composition, which includes a prepreg, a resin film, a laminate or a printed circuit board.

[0018] For example, in one embodiment, the aforementioned article has one, more or all of the following characteristics:

[0019] The dielectric constant measured at a frequency of 10 GHz according to the method described in JIS C2565 is less than or equal to 5.05;

[0020] The dielectric loss measured at a frequency of 10 GHz according to the method described in JIS C2565 is less than or equal to 0.0020;

[0021] The thermal conductivity measured according to the method described in ASTM-D5470 is greater than or equal to 1.06 W / (mK);

[0022] The copper foil tensile force measured by the method described in IPC-TM-650 2.4.8 is greater than or equal to 4.0 lb / in;

[0023] The bendability measured by the method described in JIS C 6471 is greater than or equal to 323 times;

[0024] An elongation greater than or equal to 10.1% as measured by the method described in ASTM D412; and

[0025] The edge distance is greater than or equal to 28 meters. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text have the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this specification shall prevail.

[0027] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0028] The use of "one", "a", "an" or similar expressions to describe the components and technical features of the present invention is merely for the convenience of expression and to provide a general meaning to the scope of the present invention. Therefore, such description should be understood to include one or at least one, and the singular also includes the plural, unless it is obvious that it refers to another meaning.

[0029] In this document, "or its combination" means "or any combination thereof", and "any one", "any one" means "any one", "any one" or "any one".

[0030] As used herein, the terms "include", "comprising", "having", "containing" or any other similar terms are open-ended transitional phrases, which are intended to cover non-exclusive inclusions. For example, a composition or article containing multiple elements is not limited to those elements listed herein, but may also include other elements that are not explicitly listed but are generally inherent to the composition or article. In addition, unless otherwise expressly stated, the term "or" refers to an inclusive "or" rather than an exclusive "or". For example, any of the following situations satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), and both A and B are true (or exist). In addition, as used herein, the terms "include", "comprising", "having", and "containing" should be interpreted as being specifically disclosed and simultaneously covering transitional terms such as "consisting of" and "consisting essentially of".

[0031] In this article, the terms "and", "with", "and", "as well as" or other similar terms are used to connect parallel sentence components, and there is no distinction between the previous and subsequent components. The meaning of the parallel sentence components does not change after the positions of the parallel sentence components are exchanged in grammatical sense.

[0032] In this article, all features or conditions defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible sub-ranges and individual values ​​within the range, especially integer values. For example, the range description of "1 to 8" should be deemed to have specifically disclosed all sub-ranges such as 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., especially the sub-ranges defined by all integer values, and should be deemed to have specifically disclosed individual values ​​such as 1, 2, 3, 4, 5, 6, 7, 8, etc. in the range. Similarly, the range description of "between 1 and 8" should be deemed to have specifically disclosed all ranges such as 1 to 8, 1 to 7, 2 to 8, 2 to 6, 3 to 6, 4 to 8, 3 to 8, etc., and include endpoint values. Unless otherwise specified, the above interpretation method is applicable to all contents of the full text of the present invention, regardless of whether the scope is extensive or not.

[0033] If the quantity or other numerical value or parameter is expressed as a range, a preferred range or a series of upper and lower limits, it should be understood that all ranges consisting of any upper limit or preferred value of the range and the lower limit or preferred value of the range have been specifically disclosed herein, regardless of whether such ranges are disclosed separately. In addition, if a numerical range is mentioned herein, unless otherwise specified, the range should include its endpoints and all integers and fractions within the range.

[0034] In this document, numerical values ​​should be understood to have the accuracy of the significant digits of the numerical values, provided that the purpose of the invention can be achieved. For example, the number 40.0 should be understood to cover the range from 39.50 to 40.49.

[0035] In this article, for the use of Markush groups or optional terms to describe the features or examples of the present invention, those skilled in the art should understand that subgroups or any individual members of all members in the Markush group or option list can also be used to describe the present invention. For example, if X is described as "selected from the group consisting of X1, X2 and X3", it also means that the claim that X is X1 and the claim that X is X1 and / or X2 and / or X3 have been fully described. Furthermore, for those who use Markush groups or optional terms to describe the features or examples of the present invention, those skilled in the art should understand that any combination of subgroups or individual members of all members in the Markush group or option list can also be used to describe the present invention. Accordingly, for example, if X is described as "selected from the group consisting of X1, X2 and X3", and Y is described as "selected from the group consisting of Y1, Y2 and Y3", it means that the claim that X is X1 or X2 or X3 and Y is Y1 or Y2 or Y3 has been fully described.

[0036] Unless otherwise specified, in the present invention, a compound refers to a chemical substance formed by two or more elements connected by chemical bonds, including small molecule compounds and polymer compounds, and is not limited thereto. The compound herein is not limited to a single chemical substance when interpreted, but can also be interpreted as the same type of chemical substance with the same composition or the same properties. In addition, in the present invention, a mixture refers to a combination of two or more compounds.

[0037] If not otherwise specified, the "resin" in the present invention is a customary name for a synthetic polymer, which may include monomers, polymers thereof, combinations of monomers, combinations of polymers thereof, or combinations of monomers and polymers thereof, etc., and is not limited thereto.

[0038] If not otherwise specified, in the present invention, modified products (also referred to as modified products) include: products after modification of the reactive functional groups of each resin, products after prepolymerization of each resin with other resins, products after cross-linking of each resin with other resins, products after homopolymerization of each resin, products after copolymerization of each resin with other resins, and the like.

[0039] In this article, prepolymer refers to a compound or mixture (monomer) that still contains a reactive functional group or a product with polymerization potential after prepolymerization (partial polymerization) reaction. For example, the molecular weight or viscosity can be used to assist in confirming whether the reaction degree of the prepolymerization reaction meets the requirements. The prepolymerization method used in this article, for example but not limited to, uses solvent heating to initiate prepolymerization reaction, or initiates prepolymerization reaction with hot melt reaction. For example, solvent heating prepolymerization is to add raw materials to the solvent to dissolve, and optionally add catalysts or inhibitors, wait for all raw materials to dissolve in the solvent and then heat up the reaction, thereby initiating prepolymerization reaction. For example, suitable solvents include butanone, methanol, ethanol, ethylene glycol monomethyl ether, acetone, methyl isobutyl ketone, cyclohexanone, toluene, xylene, methoxyethyl acetate, ethoxyethyl acetate, propoxyethyl acetate, ethyl acetate, propylene glycol methyl ether, dimethylformamide, dimethylacetamide, nitrogen methyl pyrrolidone or a combination thereof. Hot melt reaction prepolymerization is to directly heat and melt the raw materials to initiate prepolymerization reaction. The prepolymer product (prepolymer) has a larger molecular weight than the unprepolymerized compound monomer or mixture monomer, and can be analyzed by gel permeation chromatography (GPC). The result diagram of the retention time (X-axis) and molecular weight (Y-axis) distribution shows that the molecular weight distribution peak of the prepolymer is located at the front end (shorter retention time), while the molecular weight distribution peak of the monomer is located at the back end (longer retention time). In addition, the obtained prepolymer has a wider molecular weight distribution peak containing multiple peaks connected continuously, while the monomer has a narrower molecular weight distribution peak containing only a single molecular weight distribution peak.

[0040] For those skilled in the art, a resin composition containing two compounds A and B and an additive (comprising three components in total), and a resin composition containing a prepolymer formed by two compounds A and B and an additive (comprising two components in total) are different resin compositions, and the two are completely different in many aspects such as the preparation method, the physical and chemical properties of the compounds, and the properties of the products thereof. For example, the former is to mix A, B and the additive to form a resin composition, while the latter is to first prepolymerize the mixture including A and B under appropriate conditions to form a prepolymer, and then mix the prepolymer with the additive to obtain the resin composition. For example, for those skilled in the art, the aforementioned two resin compositions have completely different compositions, and since the function of the prepolymer formed by the two compounds A and B in the resin composition is completely different from the function of A and B individually or jointly in the resin composition, the two resin compositions should be regarded as completely different chemical substances with completely different chemical positions. For example, for those skilled in the art, since the aforementioned two resin compositions are completely different chemical substances, their products will not have the same properties. For example, a resin composition including a prepolymer formed by two compounds A and B and a crosslinking agent, since both A and B have partially reacted or converted during the prepolymerization reaction to form the prepolymer, when the resin composition is subsequently heated at a high temperature to form a semi-cured state, a partial crosslinking reaction occurs between the prepolymer and the crosslinking agent, rather than each of A and B undergoing a partial crosslinking reaction with the crosslinking agent. Therefore, the products formed by the two resin compositions will also be completely different and have completely different properties.

[0041] In this article, vinyl-containing means that the compound structure contains ethylene carbon-carbon double bonds (C=C) or their derivative functional groups. Therefore, examples of vinyl-containing compounds may include, but are not limited to, compounds containing vinyl, allyl, vinylbenzyl, methacrylate and other functional groups in the structure. Unless otherwise specified, the positions of the aforementioned functional groups are not particularly limited, and may be located at the end of a long chain structure, for example. Therefore, for example, a vinyl-containing polyphenylene ether resin represents a polyphenylene ether resin containing vinyl, allyl, vinylbenzyl, methacrylate and other functional groups, but is not limited thereto.

[0042] In this article, parts by weight represent the number of parts by weight, which can be any weight unit, such as but not limited to grams, kilograms, pounds, etc. For example, 100 parts by weight of a prepolymer can represent 100 grams of prepolymer, 100 kilograms of prepolymer, or 100 pounds of prepolymer, but is not limited thereto. In this article, if the amounts of different components are presented in a proportional relationship, the actual amounts can be any amount that meets the proportional relationship.

[0043] The following detailed description is merely illustrative in nature and is not intended to limit the present invention and its use. In addition, this document is not limited by any theory described in the above prior art or invention summary or the following detailed description or examples.

[0044] As mentioned above, the main purpose of the present invention is to provide a resin composition, which comprises 100 parts by weight of a prepolymer and 150 to 200 parts by weight of a ceramic filler, wherein:

[0045] The prepolymer is prepared by a prepolymerization reaction of a mixture, and the mixture includes a maleimide resin and a diamine compound in a molar ratio between 1:2 and 2:1;

[0046] The thermal conductivity of the ceramic filler is greater than 30 W / (mK); and

[0047] The diamine compound includes a compound having a structure shown in formula (1), a compound having a structure shown in formula (2), a compound having a structure shown in formula (3), or a combination thereof:

[0048]

[0049] wherein n1 is independently an integer from 6 to 8, and n2 is independently an integer from 5 to 8;

[0050]

[0051] The conditions of the prepolymerization reaction are not particularly limited and can be adjusted by those skilled in the art without excessive experimentation. For example, in one embodiment, the prepolymerization reaction can be carried out at a temperature of 70 to 150° C. for 1 to 20 hours in the presence of a catalyst, and the conversion rate of the prepolymerization reaction is between 10% and 90%.

[0052] For example, the prepolymerization reaction described in the present invention means that the conversion rate of the maleimide is greater than 0% and less than 100% (excluding 0% and 100%), and the conversion rate of the compound having the structure shown in formula (1), the compound having the structure shown in formula (2), the compound having the structure shown in formula (3), or a combination thereof is greater than 0% and less than 100% (excluding 0% and 100%). That is, the overall conversion rate of the maleimide and any one or more diamine compounds is greater than 0% and less than 100% (excluding 0% and 100%). In one embodiment, the overall conversion rate of the maleimide and any one or more diamine compounds is between 10% and 90%.

[0053] If not otherwise specified, catalysts suitable for the prepolymerization reaction of the aforementioned mixture may include, but are not limited to, triethylamine (TEA), pyridine, imidazole, boron trifluoride amine complex, 2-methylimidazole (2MI), 2-phenyl-1H-imidazole (2PZ), 2-ethyl-4-methylimidazole (2E4MI), 4-dimethylaminopyridine (DMAP) or tertiary amine.

[0054] In the present invention, ceramic filler refers to a type of inorganic non-metallic filler made through steps such as forming and sintering, and the bonding bonds of its constituent phases are ionic bonds, covalent bonds, or mixed bonds of ionic bonds and covalent bonds. For example, in one embodiment, the ceramic filler includes aluminum oxide, aluminum nitride, silicon carbide, boron nitride, silicon nitride, magnesium oxide, or a combination thereof. In the resin composition of the present invention, the ceramic filler can be used alone or in combination of two or more. From the viewpoint of thermal conductivity and improved dielectric properties, toughness, and bendability, the ceramic filler preferably includes boron nitride, aluminum nitride, magnesium oxide, or a combination thereof. If not otherwise specified, the shape of the ceramic filler is not particularly limited, and for example, it can be plate-like, spherical, amorphous (irregular), broken, polygonal, etc.

[0055] In the present invention, the thermal conductivity of the ceramic filler is greater than 30 W / (mK), preferably 35 W / (mK) or more. The upper limit of the thermal conductivity of the ceramic filler is not particularly limited. For those skilled in the art, the common thermal conductivity of the ceramic filler may be, for example, less than 320 W / (mK), preferably less than 200 W / (mK).

[0056] In the present invention, the type of maleimide resin applicable to the aforementioned prepolymerization reaction is not particularly limited. For example, the maleimide resin may include 4,4'-diphenylmethane bismaleimide, polyphenylmethane maleimide (or oligomer of phenylmethane maleimide), bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 3,3'-dimethyl-5,5'-dipropyl-4,4'-diphenylmethane bismaleimide, bismaleimide), m-phenylene bismaleimide, 4-methyl-1,3-phenylene bismaleimide

[0057] (4-methyl-1,3-phenylene bismaleimide), 1,6-bismaleimide-(2,2,4-trimethyl)hexane, n-2,3-dimethylphenylmaleimide

[0058] (N-2,3-xylylmaleimide), n-2,6-dimethylphenylmaleimide (N-2,6-xylylmaleimide), n-phenylmaleimide (N-phenylmaleimide), vinylbenzyl maleimide (VBM), maleimide containing biphenyl structure, maleimide resin containing aliphatic long chain structure, prepolymer of diallyl compound and maleimide resin, prepolymer of multifunctional amine and maleimide resin (multifunctional amine includes two or more amine functional groups), prepolymer of acidic phenol compound and maleimide resin or a combination thereof. Modified products of these components are also included in the interpretation.

[0059] For example, examples of maleimide resins include, but are not limited to, maleimide resins produced by Daiwakasei Industry Co., Ltd. under the trade names of BMI-1000, BMI-1000H, BMI-1100, BMI-1100H, BMI-2000, BMI-2300, BMI-3000, BMI-3000H, BMI-4000, BMI-5000, BMI-5100, BMI-TMH, BMI-7000, and BMI-7000H, or maleimide resins produced by KI Chemical Co., Ltd. under the trade names of BMI-70, BMI-80, or maleimide resins produced by Nippon Kayaku Co., Ltd. under the trade names of MIR-3000 or MIR-5000. For example, maleimide resins containing aliphatic long chain structures (e.g., containing C5 to C 50 Examples of maleimide resins having aliphatic long chain structures include, but are not limited to, maleimide resins produced by designer molecules under the trade names of BMI-689, BMI-1400, BMI-1500, BMI-1700, BMI-2500, BMI-3000, BMI-5000 and BMI-6000.

[0060] Unless otherwise specified, the aforementioned maleimide resins may be used alone or in combination of two or more.

[0061] In addition to the aforementioned components, the resin composition of the present invention may further include epoxy resin, vinyl polyphenylene ether resin, flame retardant, hardening accelerator, polymerization inhibitor, solvent, silane coupling agent, colorant, toughening agent or a combination thereof as needed.

[0062] The aforementioned epoxy resin may be any type of epoxy resin known in the art, including but not limited to, for example, bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol AD ​​epoxy resin, novolac epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, multifunctional epoxy resin, dicyclopentadiene (DCPD) epoxy resin, phosphorus-containing epoxy resin, p-xylene epoxy resin, naphthalene epoxy resin (e.g., naphthol epoxy resin), benzofuran epoxy resin, and isocyanate-modified epoxy resin. Among them, the phenolic epoxy resin can be phenol novolac epoxy resin, bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, biphenyl novolac epoxy resin, phenol benzaldehyde epoxy resin, phenolaralkyl novolac epoxy resin, o-cresol novolac epoxy resin or a copolymer of epoxy resin and silicone resin; among them, the phosphorus-containing epoxy resin can be DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) epoxy resin, DOPO-HQ epoxy resin or a combination thereof.The aforementioned DOPO epoxy resin may include DOPO-containing phenol novolac epoxy resin, DOPO-containing cresol novolac epoxy resin, DOPO-containing bisphenol-Anovolac epoxy resin or a combination thereof; the aforementioned DOPO-HQ epoxy resin may include DOPO-HQ-containing phenolnovolac epoxy resin, DOPO-HQ-containing o-cresol novolac epoxy resin, DOPO-HQ-containing bisphenol-Anovolac epoxy resin, dimer acid-modified epoxy resin or a combination thereof. Unless otherwise specified, the amount of the epoxy resin is not particularly limited, for example, it can be 4 to 20 parts by weight of epoxy resin compared to 100 parts by weight of prepolymer, preferably 4 to 12 parts by weight of epoxy resin compared to 100 parts by weight of prepolymer.

[0063] The aforementioned vinyl-containing polyphenylene ether resin may include, but is not limited to, polyphenylene ether resins containing vinyl, allyl, vinylbenzyl or methacrylate. For example, in one embodiment, the aforementioned vinyl-containing polyphenylene ether resin includes vinylbenzyl biphenyl polyphenylene ether resin, methacrylate polyphenylene ether resin (i.e., methacryloyl polyphenylene ether resin), allyl polyphenylene ether resin, vinylbenzyl modified bisphenol A polyphenylene ether resin, vinyl chain extended polyphenylene ether resin or a combination thereof. For example, the vinyl-containing polyphenylene ether resin may be a vinyl benzyl biphenyl polyphenylene ether resin having a number average molecular weight of about 1200 (e.g., OPE-2st1200, available from Mitsubishi Gas Chemical Co., Ltd.), a vinyl benzyl biphenyl polyphenylene ether resin having a number average molecular weight of about 2200 (e.g., OPE-2st 2200, available from Mitsubishi Gas Chemical Co., Ltd.), a methacrylate polyphenylene ether resin having a number average molecular weight of about 1900 to 2300 (e.g., SA9000, available from Sabic), a vinyl benzyl modified bisphenol A polyphenylene ether resin having a number average molecular weight of about 2400 to 2800, a vinyl chain-extended polyphenylene ether resin having a number average molecular weight of about 2200 to 3000, or a combination thereof. The vinyl chain-extended polyphenylene ether resin may include various types of polyphenylene ether resins disclosed in U.S. Patent Application Publication No. 2016 / 0185904A1, which is incorporated herein by reference in its entirety. If not otherwise specified, the amount of the vinyl polyphenylene ether resin is not particularly limited, for example, it can be 1 to 30 parts by weight of the vinyl polyphenylene ether resin relative to 100 parts by weight of the prepolymer, preferably 1 to 23 parts by weight of the vinyl polyphenylene ether resin relative to 100 parts by weight of the prepolymer.

[0064] For example, the flame retardant may be any one or more flame retardants suitable for use in the manufacture of prepregs, resin films, laminates or printed circuit boards, such as but not limited to phosphorus-containing flame retardants, preferably including: ammonium polyphosphate, hydroquinone bis-(diphenylphosphate), bisphenol A bis-(diphenylphosphate), tri(2-carboxyethyl)phosphine (TCEP), tri(chloroisopropyl) phosphate, trimethyl phosphate (TMP), dimethyl methyl phosphonate (DMMP), resorcinol bis(dixylenyl ... Phosphate), RDXP, such as PX-200, PX-201, PX-202 and other commercial products), phosphazene (phosphazene, such as SPB-100, SPH-100, SPV-100 and other commercial products), melamine polyphosphate, DOPO

[0065] (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and its derivatives or resins, DPPO (diphenylphosphine oxide) and its derivatives or resins, melamine cyanurate, tri-hydroxyethyl isocyanurate, aluminum phosphinate (such as OP-930, OP-935 and other products) or a combination thereof.

[0066] For example, the flame retardant may be a DPPO compound (such as a bis-DPPO compound, such as commercially available products such as PQ-60), a DOPO compound (such as a bis-DOPO compound), a DOPO resin (such as DOPO-HQ, DOPO-NQ, DOPO-PN, DOPO-BPN), a DOPO-bonded epoxy resin, etc., wherein DOPO-PN is a DOPO phenol novolac compound, and DOPO-BPN may be a bisphenol novolac compound such as DOPO-BPAN (DOPO-bisphenol A novolac), DOPO-BPFN (DOPO-bisphenol F novolac) or DOPO-BPSN (DOPO-bisphenol S novolac).

[0067] For example, the hardening accelerator (including the hardening initiator) may include a catalyst such as a Lewis base or a Lewis acid. The Lewis base may include one or more of imidazole, boron trifluoride amine complex, ethyltriphenyl phosphonium chloride, 2-methylimidazole (2MI), 2-phenyl-1H-imidazole (2PZ), 2-ethyl-4-methylimidazole (2E4MI), triphenylphosphine (TPP), 1-cyanoethyl-2-phenylimidazole (3-(2-phenyl-1H-imidazol-1-yl) propanenitrile (2PZ-CN) and 4-dimethylaminopyridine (DMAP). The Lewis acid may include a metal salt compound such as a metal salt compound of manganese, iron, cobalt, nickel, copper, zinc, etc., such as a metal catalyst such as zinc octoate and cobalt octoate. The hardening accelerator also includes a hardening initiator, such as a peroxide that can generate free radicals, and the hardening initiator includes but is not limited to: diisopropylbenzene peroxide, tert-butyl peroxybenzoate, dibenzoyl peroxide (BPO), 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne (25B) and di(tert-butylperoxyisopropyl)benzene or a combination thereof. If not otherwise specified, the amount of the hardening accelerator is not particularly limited, for example, 0.10 to 0.35 parts by weight of the hardening accelerator can be used relative to 100 parts by weight of the prepolymer.

[0068] For example, the above-mentioned inhibitor may include, but is not limited to, 1,1-diphenyl-2-trinitrophenylhydrazine, methacrylonitrile, 2,2,6,6-tetramethyl-1-oxy-piperidine, dithioester, nitrogen oxide stable free radical, triphenylmethyl free radical, metal ion free radical, sulfur free radical, hydroquinone, p-methoxyphenol, p-benzoquinone, phenothiazine, β-phenylnaphthylamine, p-tert-butylcatechol, methylene blue, 4,4'-butylenebis(6-tert-butyl-3-methylphenol) and 2,2'-methylenebis(4-ethyl-6-tert-butylphenol) or a combination thereof. For example, the above-mentioned nitrogen oxide stable free radical may include, but is not limited to, nitrogen oxide free radicals from cyclic hydroxylamines such as 2,2,6,6-substituted-1-piperidinyloxy free radical or 2,2,5,5-substituted-1-pyrrolidinyloxy free radical. As a substituent, it is preferably an alkyl group with a carbon number of 4 or less such as methyl or ethyl. Specific nitrogen oxide free radical compounds are not limited, and examples include but are not limited to 2,2,6,6-tetramethyl-1-piperidinyloxy free radicals, 2,2,6,6-tetraethyl-1-piperidinyloxy free radicals, 2,2,6,6-tetramethyl-4-oxo-1-piperidinyloxy free radicals, 2,2,5,5-tetramethyl-1-pyrrolidinyloxy free radicals, 1,1,3,3-tetramethyl-2-isoindolinyloxy free radicals, N,N-di-tert-butylamineoxy free radicals, etc. Stable free radicals such as galvinoxyl free radicals can also be used to replace nitrogen oxide free radicals. The inhibitor suitable for the resin composition of the present invention can also be a product derived from the hydrogen atom or atomic group in the inhibitor being replaced by other atoms or atomic groups. For example, the hydrogen atom in the inhibitor is replaced by an atomic group such as an amino group, a hydroxyl group, a ketocarbonyl group, etc.

[0069] For example, the solvent applicable to the resin composition of the present invention is not particularly limited, and can be any solvent suitable for dissolving the resin composition of the present invention, including but not limited to: methanol, ethanol, ethylene glycol monomethyl ether, acetone, butanone (also known as methyl ethyl ketone), methyl isobutyl ketone, cyclohexanone, toluene, xylene, methoxyethyl acetate, ethoxyethyl acetate, propoxyethyl acetate, ethyl acetate, dimethylformamide, dimethylacetamide, propylene glycol methyl ether and the like solvents or mixed solvents thereof. The amount of the aforementioned solvent is not particularly limited, and the amount of the solvent added can be adjusted according to the required viscosity of the resin composition.

[0070] For example, the silane coupling agent may include a silane compound (such as but not limited to a siloxane compound), which may be further divided into an amino silane compound, an epoxy silane compound, a vinyl silane compound, an acrylate silane compound, a methacrylate silane compound, a hydroxy silane compound, an isocyanate silane compound, a methacryloxy silane compound, and an acryloxy silane compound according to the type of functional group.

[0071] For example, the coloring agent may include but is not limited to dye or pigment.

[0072] In the present invention, the main function of adding a toughening agent is to improve the toughness of the resin composition. For example, the toughening agent may include but is not limited to carboxyl-terminated butadieneacrylonitrile rubber (CTBN), core-shell rubber, and other compounds or combinations thereof.

[0073] The resin compositions of the aforementioned embodiments can be made into various products, such as components suitable for various electronic products, including but not limited to prepregs, resin films, laminates or printed circuit boards.

[0074] For example, the resin composition of each embodiment of the present invention can be made into a semi-cured sheet, which includes a reinforcing material and a layered object arranged on the reinforcing material. The layered object is obtained by heating the aforementioned resin composition at a high temperature to form a semi-cured state (B-stage). The baking temperature for making the semi-cured sheet is between 80°C and 150°C, preferably between 100°C and 120°C. The reinforcing material can be any one of a fiber material, a woven fabric, and a non-woven fabric, and the woven fabric preferably includes a glass fiber cloth. The type of glass fiber cloth is not particularly limited, and can be a commercially available glass fiber cloth that can be used for various printed circuit boards, such as E-type glass cloth, D-type glass cloth, S-type glass cloth, T-type glass cloth, L-type glass cloth or Q-type glass cloth, wherein the types of fibers include yarn and roving, etc., and the form may include open fiber or unopen fiber. The aforementioned non-woven fabric preferably includes a liquid crystal resin non-woven fabric, such as a polyester non-woven fabric, a polyurethane non-woven fabric, etc., and is not limited thereto. The aforementioned fabric may also include a liquid crystal resin fabric, such as a polyester fabric or a polyurethane fabric, and is not limited thereto. This reinforcing material can increase the mechanical strength of the prepreg. In a preferred embodiment, the reinforcing material can also be selectively pretreated with a silane coupling agent. The prepreg is subsequently heated and cured (C-stage) to form an insulating layer.

[0075] For example, the resin composition of each embodiment of the present invention can be made into a resin film, which is obtained by semi-curing the aforementioned resin composition after baking and heating. The resin composition can be selectively coated on a polyethylene terephthalate film (PET film), a polyimide film (PI film), a copper foil or a copper foil with adhesive, and then baked and heated at a temperature of 100° C. to 120° C. for 5 to 15 minutes to form a semi-cured state, so that the resin composition forms a resin film.

[0076] For example, the resin composition of each embodiment of the present invention can be made into a laminate, which includes two metal foils and an insulating layer disposed between the metal foils. The insulating layer can be obtained by curing (C-stage) the resin composition under high temperature and high pressure conditions, wherein the suitable curing temperature can be between 180°C and 240°C, preferably between 200°C and 220°C, and the curing time is 80 to 140 minutes, preferably 90 to 120 minutes. The insulating layer can be formed by curing (C-stage) the semi-cured sheet or resin film. The metal foil can include copper, aluminum, nickel, platinum, silver, gold or their alloys, for example, the metal foil can be copper foil. In one embodiment, the laminate is a copper clad laminate (CCL).

[0077] In addition, the aforementioned laminate can be further processed through a circuit manufacturing process to form a circuit board, such as a printed circuit board.

[0078] In one embodiment, the resin composition provided by the present invention can improve at least one of the following properties: dielectric constant, dielectric loss, thermal conductivity, copper foil tension, edge relief distance, bendability, elongation, etc.

[0079] For example, the resin composition provided by the present invention or the product made therefrom may satisfy one, more or all of the following characteristics:

[0080] The dielectric constant measured at a frequency of 10 GHz according to the method described in JIS C2565 is less than or equal to 5.05, for example, the dielectric constant is between 4.13 and 5.05;

[0081] The dielectric loss measured at a frequency of 10 GHz according to the method described in JIS C2565 is less than or equal to 0.0020, for example, the dielectric loss is between 0.0013 and 0.0020;

[0082] The thermal conductivity measured according to the method described in ASTM-D5470 is greater than or equal to 1.06 W / (mK), for example, the thermal conductivity is between 1.06 W / (mK) and 1.76 W / (mK);

[0083] The copper foil tensile force measured by the method described in IPC-TM-650 2.4.8 is greater than or equal to 4.0 lb / in, for example, the copper foil tensile force is between 4.0 lb / in and 4.7 lb / in;

[0084] The bendability measured by the method described in JIS C 6471 is greater than or equal to 323 times, for example, the bendability is between 323 times and 487 times;

[0085] An elongation greater than or equal to 10.1% as measured by the method described in ASTM D412, such as an elongation between 10.1% and 16.6%; and

[0086] The edge distance is greater than or equal to 28 meters, for example, the edge distance is between 28 meters and 31 meters.

[0087] The measurement methods of the aforementioned characteristics will be described in detail later in this article.

[0088] Various prepolymers were prepared according to the textual description of Preparation Examples 1 to 12, wherein the monomers used in the prepolymerization reaction and their amounts (molar ratios) can be found in Tables 1 and 2. In addition, various raw materials from the following sources were used to prepare the resin compositions of the Examples of the present invention and the Comparative Examples of the present invention according to the amounts shown in Tables 3 to 7, and further prepared into various test samples.

[0089] The chemical raw materials used in the manufacturing examples of prepolymers, the examples of resin compositions and the comparative examples of resin compositions are as follows:

[0090] BMI-80: bisphenol A diphenyl ether bismaleimide, purchased from KI Chemicals.

[0091] BMI-TMH: 1,6-bismaleimide-(2,2,4-trimethyl)hexane, purchased from Sichuan Dongcai.

[0092] Compound of formula (1): diamine compound, with the following structure, purchased from Mitsui Chemicals.

[0093]

[0094] Compound of formula (2-1): diamine compound, with the following structure, purchased from Qingtai Enterprise.

[0095]

[0096] Compound of formula (2-2): diamine compound, with the following structure, purchased from Qingtai Enterprise.

[0097]

[0098] Compound of formula (2-3): diamine compound, with the following structure, purchased from Qingtai Enterprise.

[0099]

[0100] Compound of formula (3): diamine compound, the structure of which is as follows, purchased from Dongxin Chemical.

[0101]

[0102] ODA: 4,4'-diaminodiphenyl ether, commercially available.

[0103] Triethylamine: TEA, N,N-diethylethanamine, is commercially available.

[0104] MEK: butanone (also known as methyl ethyl ketone), commercially available.

[0105] BN: Boron nitride, thermal conductivity 60 W / (mK), available from Tokuyama Corporation.

[0106] AlN: aluminum nitride, thermal conductivity of 180 W / (mK), available from Tokuyama Corporation.

[0107] MgO: magnesium oxide, thermal conductivity of 36 W / (mK), purchased from UBE Corporation.

[0108] ZnO: zinc oxide, thermal conductivity of 10 W / (mK), purchased from Liuhe Chemical.

[0109] SiO2: silicon dioxide, with a thermal conductivity of 5 W / (mK), purchased from ADAMATECH.

[0110] NC-3000: biphenyl-containing epoxy resin, purchased from Nippon Kayaku Co., Ltd.

[0111] BE-188: bisphenol A epoxy resin, purchased from Changchun Resin.

[0112] Albiflex 297: epoxy-silicone copolymer, available from Evonik.

[0113] SA9000: polyphenylene ether resin containing methacrylate, purchased from Sabic.

[0114] 2PZ-CN: 1-cyanoethyl-2-phenylimidazole, purchased from Shikoku Chemical.

[0115] Production Example 1

[0116] Add BMI-80 and the compound of formula (1) (molar ratio of 2:1) into a three-necked flask, and add triethylamine (as a catalyst, other catalysts such as pyridine, imidazole, boron trifluoride amine complex, 2-methylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 4-dimethylaminopyridine or tertiary amine) as needed, and then add an appropriate amount of MEK (as a solvent, other solvents such as methanol, ethanol, ethylene glycol monomethyl ether, acetone, methyl isobutyl ketone, cyclohexanone, toluene, xylene, methoxyethyl acetate, ethoxyethyl acetate, propoxyethyl acetate, ethyl acetate, propylene glycol methyl ether, dimethylformamide, dimethylacetamide, nitrogen methyl pyrrolidone or a combination thereof) and continue stirring to obtain a mixed solution. The mixed solution is heated from room temperature to 90° C. and stirred for 4 hours, then cooled to room temperature, filtered to remove impurities, and a prepolymer solution with a solid content of about 55% is obtained, which is the prepolymer 1 of the present invention.

[0117] Production Example 2

[0118] The method is basically the same as Preparation Example 1, except that the compound of formula (1) is replaced by the compound of formula (2-1), and the prepolymer 2 of the present invention is obtained after synthesis.

[0119] Production Example 3

[0120] The method is basically the same as Preparation Example 1, except that the compound of formula (1) is replaced by the compound of formula (2-2), and the prepolymer 3 of the present invention is obtained after synthesis.

[0121] Production Example 4

[0122] The method is basically the same as Preparation Example 1, except that the compound of formula (1) is replaced by the compound of formula (2-3), and the prepolymer 4 of the present invention is obtained after synthesis.

[0123] Production Example 5

[0124] The method is basically the same as Preparation Example 1, except that BMI-TMH and the compound of formula (3) (molar ratio of 2:1) are used for prepolymerization to obtain the prepolymer 5 of the present invention.

[0125] Production Example 6

[0126] The method is basically the same as that of Preparation Example 1, except that BMI-80 is replaced by BMI-TMH, and the prepolymer 6 of the present invention is obtained after synthesis.

[0127] Production Example 7

[0128] The method is basically the same as Preparation Example 1, except that BMI-80, the compound of formula (1) and the compound of formula (2-1) (molar ratio of 4:1:1) are used for prepolymerization to obtain the prepolymer 7 of the present invention.

[0129] Production Example 8

[0130] The method is basically the same as Preparation Example 1, except that the molar ratio of BMI-80 to the compound of formula (1) is 1:1, and the prepolymer 8 of the present invention is obtained after synthesis.

[0131] Production Example 9

[0132] The method is basically the same as Preparation Example 1, except that the molar ratio of BMI-80 to the compound of formula (1) is 1:2, and the prepolymer 9 of the present invention is obtained after synthesis.

[0133] Production Example 10

[0134] The process is basically the same as that of Preparation Example 1, except that the compound of formula (1) is replaced by ODA, and prepolymer 10 is obtained after synthesis.

[0135] Production Example 11

[0136] The method is basically the same as that of Preparation Example 1, except that the molar ratio of BMI-80 to the compound of formula (1) is 1:4. Prepolymer 11 is obtained after synthesis.

[0137] Production Example 12

[0138] The method is basically the same as that of Preparation Example 1, except that the molar ratio of BMI-80 to the compound of formula (1) is 4:1, and prepolymer 12 is obtained after synthesis.

[0139] [Table 1] Monomers involved in different prepolymers and their amounts (molar ratio)

[0140]

[0141]

[0142] [Table 2] Monomers involved in different prepolymers and their amounts (molar ratio)

[0143] monomer Prepolymer 7 Prepolymer 8 Prepolymer 9 Prepolymer 10 Prepolymer 11 Prepolymer 12 BMI-80 4 1 1 2 1 4 BMI-TMH Formula (1) 1 1 2 4 1 Formula (2-1) 1 Formula (2-2) Formula (2-3) Formula (3) ODA 1

[0144] The compositions (parts by weight) and property tests of the resin compositions of the embodiments and comparative examples are shown below.

[0145] [Table 3] Composition (unit: weight parts) and characteristic tests of the resin composition of the embodiment

[0146]

[0147] [Table 4] Composition (unit: weight parts) and property tests of the resin composition of the embodiment

[0148]

[0149] [Table 5] Composition (unit: weight parts) and characteristic tests of the resin composition of the embodiment

[0150]

[0151] [Table 6] Composition (unit: weight parts) and characteristic tests of comparative resin compositions

[0152]

[0153] [Table 7] Composition (unit: weight parts) and property tests of comparative resin compositions

[0154]

[0155] The above characteristics are prepared by referring to the following method to prepare the object to be tested (sample), and then the characteristics are analyzed according to specific conditions.

[0156] 1. Resin film: The resin compositions of the embodiment and the comparative example (in parts by weight) were respectively used, and each resin composition was added into a stirring tank and mixed evenly to form a varnish, which was then coated onto a copper foil (trade name MT18Ex, containing 18 micron carrier copper foil and 3 micron thin copper, purchased from Mitsui Metal) to make the resin composition adhere evenly, and then heated and baked at a temperature of 100° C. for 10 minutes, and then the 18 micron carrier copper foil was removed, and then the 3 micron thin copper was removed by etching to obtain a resin film with a thickness of 32.5 microns.

[0157] 2. Prepreg (PP): Use the resin compositions of the embodiment and the comparative example (in parts by weight) respectively, add the components of the resin composition into a stirring tank and mix them evenly to form a varnish. Place the varnish into an impregnation tank, and then immerse a glass fiber cloth (e.g., L-glass fiber cloth (L-glass fiber fabric) with a specification of 1078, purchased from Xinyue Company) into the impregnation tank to make the resin composition adhere to the glass fiber cloth, and then heat it at 100°C to 120°C to a semi-cured state (B-Stage), to obtain a prepreg, whose resin content is about 80%.

[0158] 3. Copper-containing substrate 1 (formed by pressing a prepreg): prepare two 1-ounce HTE (High Temperature Elongation) copper foils and a 1078-gauge L-glass fiber cloth impregnated with the prepregs made from the samples to be tested (each group of embodiments or each group of comparative examples), and the resin content of each prepreg is about 80%. Copper foil, a prepreg and copper foil are stacked in order, and pressed for 90 minutes to 120 minutes under vacuum conditions, a pressing pressure of 250 psi to 600 psi and a temperature of 200° C. to 220° C. to form a copper-containing substrate 1. Among them, a prepreg is cured to form an insulating layer between the two copper foils, and the resin content of the insulating layer is about 80%.

[0159] 4. Copper-containing substrate 2 (formed by pressing two prepregs): The preparation method is basically the same as that of copper-containing substrate 1, except that the insulating layer is formed by curing the two prepregs.

[0160] 5. Copper-containing substrate 3 (formed by pressing six prepregs): the preparation method is basically the same as that of copper-containing substrate 1, except that the insulating layer is formed by curing six prepregs.

[0161] 6. Copper-containing substrate 4 (formed by pressing eight prepregs): the preparation method is basically the same as that of copper-containing substrate 1, except that the insulating layer is formed by curing eight prepregs.

[0162] 7. Copper-free substrate 1 (formed by pressing two prepregs together): The copper-containing substrate 2 formed by pressing two prepregs together is etched to remove the copper foil on both sides, thereby obtaining a copper-free substrate 1 (formed by pressing two prepregs together).

[0163] 8. Copper-free substrate 2 (formed by pressing eight prepregs): The copper-containing substrate 4 formed by pressing eight prepregs is etched to remove the copper foil on both sides, thereby obtaining a copper-free substrate 2 (formed by pressing eight prepregs).

[0164] For the above-mentioned samples to be tested, the test methods and their characteristic analysis items are described as follows:

[0165] Dielectric constant (Dk)

[0166] In the measurement of the dielectric constant, the copper-free substrate 1 (made of two semi-cured sheets pressed together, with a resin content of about 80%) is selected as the sample to be tested. A microwave dielectrometer (purchased from AET Company of Japan) is used to measure each sample to be tested at room temperature (about 25°C) and at a frequency of 10 GHz, referring to the method described in JIS C2565. At a measurement frequency of 10 GHz, for low dielectric constant materials, a difference in Dk values ​​of less than 0.3 indicates that there is no significant difference in the dielectric constant of the substrate (there is no significant technical difficulty), and a difference in Dk values ​​of greater than or equal to 0.3 indicates that there is a significant difference between the dielectric constants of different substrates (there is a significant technical difficulty).

[0167] Dielectric loss (dissipation factor, Df)

[0168] In the measurement of dielectric loss, the above-mentioned copper-free substrate 1 (made of two semi-cured sheets pressed together, with a resin content of about 80%) is selected as the sample to be tested. A microwave dielectrometer (purchased from AET Company of Japan) is used to measure each sample to be tested at room temperature (about 25°C) and at a frequency of 10GHz with reference to the method described in JIS C2565 to obtain the dielectric loss. The lower the dielectric loss, the better the dielectric properties of the sample to be tested. For samples with a measurement frequency of 10GHz and a Df value between 0.0010 and 0.0030, a difference in Df value of less than 0.0005 indicates that there is no significant difference in the dielectric loss of the substrate (there is no significant technical difficulty), and a difference in Df value greater than or equal to 0.0005 indicates that there is a significant difference between the dielectric losses of different substrates (there is a significant technical difficulty).

[0169] Thermal conductivity (Tk)

[0170] The above-mentioned copper-free substrate 2 (composed of eight prepregs pressed together) was selected as the sample to be tested (size: 31 mm in length, 31 mm in width, 0.85 mm in height), and each sample to be tested was measured with reference to the method described in ASTM-D5470. The above-mentioned sample was heated from room temperature (about 25°C) on the test device. At 30 minutes after heating and when the temperature was 80°C, a thermal conductivity coefficient measuring instrument (model LW-9091ir, purchased from Taiwan Ruiling Technology) was used to calculate the thermal conductivity analysis value to obtain the thermal conductivity coefficient. The unit of thermal conductivity coefficient is W / (mK). In this field, a difference in Tk value of less than 0.1W / (mK) means that there is no significant difference in the thermal conductivity coefficient of the substrate (there is no significant technical difficulty), and a difference in Tk value of greater than or equal to 0.1W / (mK) means that there is a significant difference between the thermal conductivity coefficients of different substrates (there is a significant technical difficulty).

[0171] Copper foil pull (1 oz peeling strength, 1 oz P / S)

[0172] The copper-containing substrate 3 (six prepregs pressed together) was selected and cut into rectangular samples with a width of 24 mm and a length greater than 60 mm, and the surface copper foil was etched, leaving only a long strip of copper foil with a width of 3.18 mm and a length greater than 60 mm. The universal tensile strength tester was used to measure the force required to pull 1 ounce of copper foil away from the surface of the substrate insulation layer at room temperature (about 25°C) in accordance with the method described in IPC-TM-650 2.4.8, and the unit was lb / in. In this field, the higher the copper foil tension, the better. For copper foil substrates with dielectric loss values ​​between 0.0010 and 0.0030 at a frequency of 10 GHz, a difference in copper foil tension greater than or equal to 0.4 lb / in indicates that there is a significant difference in copper foil tension for different substrates (there is a significant technical difficulty).

[0173] Routing distance

[0174] The above-mentioned copper-containing substrate 1 (formed by pressing a semi-cured sheet) is selected as the sample to be tested (the size is 18 inches long and 16 inches wide), and a CNC forming machine (edge-cutting machine) with a model number of TQZX-II is used to mill the sample according to the designed pattern with a milling cutter (product name: DCR-1700) with a diameter of 1.6 mm. The milling is stopped after the needle of the milling cutter breaks, and the total length of the pattern passed by the milling cutter when the needle breaks is measured, and the unit is meter (m). As far as this field is concerned, the longer the edge-cutting distance, the better, which means that the wear resistance of the milling cutter is greater, the cost of consumables is lower, and the toughness is better. The difference in edge-cutting distance is greater than or equal to 3 meters, which means that there is a significant difference in the edge-cutting distance of the substrate (there is a significant technical difficulty).

[0175] Bending ability

[0176] The copper-free substrate 1 (made of two prepregs pressed together) was selected as the sample to be tested. After etching the circuit, a bending resistance test was performed using a folding tester according to the method described in JIS C 6471. The bending was performed at a curvature radius of 1.0 mm, a bending angle of 180 degrees, and a bending speed of 60 times / minute, and the number of bends until the circuit was broken was measured. A difference in the number of bends greater than or equal to 35 times indicates that there is a significant difference in the bendability of the substrate (there is a significant technical difficulty).

[0177] Elongation

[0178] The above resin film was selected as the sample to be tested. Using a universal tensile strength tester, refer to the method described in ASTM D412, and measure the elongation of the sample at break at a tensile rate of 50.8 mm / min. An elongation difference greater than or equal to 1% indicates that there is a significant difference in the elongation of the resin film (there is a significant technical difficulty).

[0179] According to the above test results, the following phenomena can be observed.

[0180] The resin compositions of Comparative Examples C1 to C5 do not contain any prepolymers, but instead use a monomer combination of maleimide resin and diamine compound. The products fail to meet the requirements in at least one of the properties such as dielectric constant, dielectric loss, copper foil tension, hemming distance, bendability, and elongation.

[0181] The resin compositions of Comparative Examples C6 and C7 do not use ceramic fillers with a thermal conductivity greater than 30 W / (mK), but use fillers with a thermal conductivity less than 30 W / (mK). The products fail to meet the requirements in at least one of the properties such as dielectric constant, dielectric loss, thermal conductivity, flange distance, bendability, and elongation.

[0182] In the resin compositions of Comparative Examples C8 and C9, the amount of ceramic filler used is not within the range of 150 to 200 parts by weight, and the products fail to meet the requirements in at least one of the properties of dielectric loss, thermal conductivity, copper foil tension, flange distance, bendability, and elongation.

[0183] The resin compositions of comparative examples C10 to C12 do not contain the prepolymer of the present invention, but use other types of prepolymers. The products fail to meet the requirements in at least one of the properties such as dielectric constant, dielectric loss, thermal conductivity, copper foil tension, flange distance, bendability, and elongation.

[0184] In comparison, the resin composition of the present invention, such as Examples E1 to E15, can simultaneously achieve at least one, multiple or all of the following properties: dielectric constant less than or equal to 5.05, dielectric loss less than or equal to 0.0020, thermal conductivity greater than or equal to 1.06W / (mK), copper foil tension greater than or equal to 4.0lb / in, bendability greater than or equal to 323 times, elongation greater than or equal to 10.1%, and hemming distance greater than or equal to 28 meters.

[0185] The above embodiments are essentially only for auxiliary explanation and are not intended to limit the embodiments of the application or the application or use of these embodiments. In this article, the term "exemplary" means "as an example, example or illustration". Any exemplary embodiment in this article is not necessarily interpreted as being better or more advantageous than other embodiments.

[0186] In addition, although at least one exemplary embodiment or comparative example has been proposed in the aforementioned embodiments, it should be understood that the present invention can still have a large number of variations. It should also be understood that the embodiments described herein are not intended to limit the scope, use or configuration of the requested application object in any way. On the contrary, the aforementioned embodiments will provide a simple guide for those skilled in the art to implement one or more of the embodiments described. Furthermore, various changes can be made to the functions and arrangements of the components without departing from the scope defined by the claims, and the claims include known equivalents and all foreseeable equivalents at the time of filing the present patent application.

Claims

1. A resin composition, characterized in that The invention comprises 100 parts by weight of a prepolymer and 150 to 200 parts by weight of a ceramic filler, wherein: The prepolymer is prepared by a prepolymerization reaction of a mixture, and the mixture includes a maleimide resin and a diamine compound in a molar ratio between 1:2 and 2:1; The thermal conductivity of the ceramic filler is greater than 30 W / (mK); and The diamine compound includes a compound having a structure shown in formula (1), a compound having a structure shown in formula (2), a compound having a structure shown in formula (3), or a combination thereof: wherein n1 is independently an integer from 6 to 8, and n2 is independently an integer from 5 to 8; 2. The resin composition according to claim 1, characterized in that The ceramic filler includes aluminum oxide, aluminum nitride, silicon carbide, boron nitride, silicon nitride, magnesium oxide or a combination thereof.

3. The resin composition according to claim 1, characterized in that The thermal conductivity of the ceramic filler is greater than 30 W / (mK) and less than 320 W / (mK).

4. The resin composition according to claim 1, characterized in that The mixture is prepolymerized at a temperature of 70 to 150° C. for 1 to 20 hours to prepare the prepolymer.

5. The resin composition according to claim 1, characterized in that The conversion rate of the maleimide resin and the diamine compound is between 10% and 90%.

6. The resin composition according to claim 1, characterized in that The maleimide resin includes 4,4'-diphenylmethane bismaleimide, polyphenylmethane maleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 3,3'-dimethyl-5,5'-dipropyl-4,4'-diphenylmethane bismaleimide, meta-phenylene bismaleimide, 4-methyl-1,3-phenylene bismaleimide, 1,6- Bismaleimide-(2,2,4-trimethyl)hexane, n-2,3-dimethylphenylmaleimide, n-2,6-dimethylphenylmaleimide, n-phenylmaleimide, vinylbenzylmaleimide, maleimide containing a biphenyl structure, maleimide containing an aliphatic long chain structure, a prepolymer of a diallyl compound and maleimide, a prepolymer of a multifunctional amine and maleimide, a prepolymer of an acidic phenol compound and maleimide, or a combination thereof.

7. The resin composition according to claim 1, characterized in that The resin composition further comprises epoxy resin, vinyl polyphenylene ether resin, flame retardant, hardening accelerator, polymerization inhibitor, solvent, silane coupling agent, colorant, toughening agent or a combination thereof.

8. A product made from the resin composition according to claim 1, characterized in that: The product includes a prepreg, a resin film, a laminate or a printed circuit board.

9. The product according to claim 8, characterized in that The dielectric constant of the product measured at a frequency of 10 GHz according to the method described in JIS C2565 is less than or equal to 5.

05.

10. The product according to claim 8, characterized in that The dielectric loss of the product measured at a frequency of 10 GHz according to the method described in JIS C2565 is less than or equal to 0.0020.

11. The product according to claim 8, characterized in that The thermal conductivity of the product measured according to the method described in ASTM-D5470 is greater than or equal to 1.06 W / (mK).

12. The article according to claim 8, characterized in that The copper foil tensile force of the product measured according to the method described in IPC-TM-6502.4.8 is greater than or equal to 4.0 lb / in.

13. The article according to claim 8, characterized in that The product has a bendability of 323 times or more as measured by the method described in JIS C 6471.

14. The article according to claim 8, characterized in that The elongation of the article measured according to the method described in ASTM D412 is greater than or equal to 10.1%.

15. The article according to claim 8, characterized in that The edge distance of the product is greater than or equal to 28 meters.